PELAYANAN PEMBUATAN AKTA KELAHIRAN ANAK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKANBARU - Putri, Fidya Dwi; Mashur, Dadang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The government must provide public services to the public, this is because the best service is the right of the community. one of the services at the Office of Population and Civil Registration of Pekanbaru City which often experience problems is in making birth certificates of children. Child birth certificate service is made by some people who complain because of the long settlement time and mistake in writing the name in issuing birth certificate.The concept of theory that researchers use is public service according to Surjadi (2009) where using standard indicator of public service, service procedure, completion time, service cost, service product, facilities and infrastructure, and competence of officer and factors influencing service of birth certificate, This research is a qualitative research with descriptive method. The selection of informants of this study using purposive sampling technique in which this informant is predetermined and the determination of informants based on the consideration that the selected informant is the people who know and get involved. Techniques of collecting data through interviews, documentation, and observation.The result of this research is that the service of making birth certificate of children at the Office of Population and Civil Registration of Pekanbaru City has not been accordingly seen from the indicators of public service standards covering the completion time, product service, facilities and infrastructure, and competence of officers and factors that influence service of making birth certificate of child to include lack of public awareness and poor staff response. Keywords: Public Service, Birth Certificate, Population Administration